Bridging the Financial Divide: Factors That Influence Financial Exclusion amongst The Unbanked Population of Botswana - Gaone Geoffrey Seleka (IJEBD (International Journal of Entrepreneurship and Business Development))
Purpose: The aim of this research is to determine the primary causes behind the unbanked population's exclusion from Botswana's official financial system.  The study aims to address the following research question: What are the main causes of the unbanked population's exclusion from Botswana's formal financial system, and how do these causes affect financial inclusion?